An Amish husband for Tillie - Lillard, Amy (Lillard, Amy. Pontotoc Mississippi series., 2020)
"Tillie Gingerich is so in love with Melvin Yoder that she agrees to leave her conservative Amish home to live with him in the English world. But when the struggle to make ends meet leads to conflict, and reveals troubling weaknesses in their relationship, Tillie returns to Pontotoc--pregnant and unmarried. Her loving family accepts her, but to convince the rest of the community, they must turn to the bishop. Distraught, Tillie runs away on Christmas Eve--only to get as far as an isolated house on the edge of town. Levi Yoder, Melvin's upright distant cousin, is grieving the loss of his wife and wants to be alone. He is hardly pleased to open his door and find a pregnant woman--a painful reminder of all he's lost. But with an ice storm approaching, he can't turn Tillie away. Yet as morning nears, the miracle of Christmas brings unexpected challenges, opportunities--and promises for the future..." --